2020
DOI: 10.1002/app.49367
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and characterization of poly(vinylidene fluoride)‐13X zeolite mixed matrix membranes for lithium ion batteries' separator with enhanced performance

Abstract: 13X zeolite was hydrothermally synthesized and poly(vinylidene fluoride) (PVDF)/13X zeolite particles mixed matrix membranes were prepared using phase inversion method as the lithium‐ion battery separator. Hydrophilic and porous 13X zeolite loading impacts on the critical separator properties of morphology, wettability, electrolyte uptake, and high temperatures dimensional stability were investigated using scanning electron microscopy, contact angle, and thermal shrinkage analysis. Electrolyte uptake of the 13… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 77 publications
0
8
0
Order By: Relevance
“…It was found that PVDF‐hexafluoropropylene (HFP) formed after the copolymerization of PVDF and HFP exhibits a significantly reduced crystallinity and increased ionic conductivity at room temperature for supercapacitor systems 18, 20, 21. PVDF provides a polymer skeleton for the polymer member because of its high crystallinity and good mechanical strength, and its high dielectric constant promotes the dissociation of electrolyte salts, increases the carrier concentration, and improves ionic conductivity 22–25, while the HFP chain is amorphous, which increases the proportion of the amorphous region in the polymer matrix that contributes to ion conduction 26, 27. Therefore, PVDF‐HFP is one of the best materials for a polymer electrolyte matrix.…”
Section: Introductionmentioning
confidence: 99%
“…It was found that PVDF‐hexafluoropropylene (HFP) formed after the copolymerization of PVDF and HFP exhibits a significantly reduced crystallinity and increased ionic conductivity at room temperature for supercapacitor systems 18, 20, 21. PVDF provides a polymer skeleton for the polymer member because of its high crystallinity and good mechanical strength, and its high dielectric constant promotes the dissociation of electrolyte salts, increases the carrier concentration, and improves ionic conductivity 22–25, while the HFP chain is amorphous, which increases the proportion of the amorphous region in the polymer matrix that contributes to ion conduction 26, 27. Therefore, PVDF‐HFP is one of the best materials for a polymer electrolyte matrix.…”
Section: Introductionmentioning
confidence: 99%
“…177,178 Zeolites are also used in the development of nanocomposite separators, with the goal of increasing the wettability and electrolyte uptake of the membranes, as well as to improve their stability at high temperatures. 179,180 Zeolites, such as 13X, 179 ZSM-5 180,181 and 4A, 182 have been used…”
Section: Zeolitesmentioning
confidence: 99%
“…The ionic conduction of the separators is a direct consequence of their wettability and uptake, as the electrolyte plays a key role on the electrochemical properties of the system. In this regard, composite separators are intensively used, and different combinations of polymer matrix and specific fillers are being developed, such as, boehmite/polyacrylonitrile (BM/PAN) [219], 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide (DOPO) into polyacrylonitrile (PAN) [220], PVDF containing titanium dioxide (TiO 2 ) and graphene oxide (GO) [189], PVDF with 13X zeolite [195] and PVDF with modacrylic and SiO 2 [221], polyacrylonitrile (PAN)/helical carbon nanofibers(HCNFs)@PVDF/UiO-66 composite [222], cellulose/Poly (vinylidene fluoride-hexafluoropropylene) membrane with titania nanoparticles [202], polyimide (PI) with ZSM-5 zeolite as filler [190] and PVDF with titanium hydroxide (Ti(OH) x ) [223], polyethylene terephthalate (PET) combined with inorganic zirconia (ZrO 2 ) [224], silica-coated expanded polytetrafluoroethylene separator [225], poly(vinyl alcohol) (PVA) with ZrO 2 nanoparticles [226], poly(vinyl alcohol) (PVA) with submicron spindle-shaped CaCO 3 [227], poly(vinyl alcohol)/melamine composite nanofiber membrane containing LATP nanocrystals [228], and poly(m-phenylene isophthalamide) (PMIA) with SiO 2 nanoparticles [229], among others, mainly with the main focus on improving the electrochemical properties. In particular, separators based on PVDF coated with ZnO have been developed with higher ionic conductivity (2.261 mS•cm −1 ), high porosity (85.1%), favorable electrolyte wettability (352%), and lower interfacial impedance (220 Ω) [198].…”
Section: Separator Membranementioning
confidence: 99%